Isolation and genetic characterization of H13N8 low pathogenic avian influenza virus from migratory birds in eastern China. Issue 1 (22nd October 2018) - Yu, Zhijun; Gao, Yuwei; He, Hongbin; Zhao, Yongkun; Yuan, Xiaoyuan; Cheng, Kaihui
Summary: Low pathogenic avian influenza virus (LPAIV) is an important zoonotic pathogen. Migratory birds are the natural reservoir for all 16 haemagglutinin (HA) and nine neuraminidase (NA) subtypes of LPAIV. Surveillance of LPAIV in migratory waterfowl and poultry is important for animal and public health. An understanding of the ecology and epidemiology of LPAI viruses in their reservoirs is beneficial for routine surveillance projects. Here, we report the isolation of an H13N8 LPAIV from black‐tailed gulls in eastern China. Full genome sequences of this isolate were determined. Genetic analysis of the HA and NA segments of this isolate showed that this H13N8 LPAIV was derived from the Eurasian lineage. Additionally, we speculate that this H13N8 LPAIV was a reassortant between the North American and Eurasian lineages. Interestingly, we identified amino acid motifs responsible for increased virulence or transmission of influenza viruses in mammals. We also found weak but measurable haemagglutination inhibition antibody titers against H13N8 virus in serum samples collected from chickens. These results suggest that continued surveillance for LPAI viruses in migratory birds and poultry is required.